2011
DOI: 10.3109/00498254.2011.552649
|View full text |Cite
|
Sign up to set email alerts
|

In vitrometabolism and transport of the new dipeptidyl peptidase 4 inhibitors, KR66222 and KR66223

Abstract: We investigated the in vitro metabolism and transport of KR66222 and KR66223, new inhibitors of dipeptidyl peptidase (DPP) 4, using human liver microsomes (HLMs) and a Caco-2 cell monolayer. Human liver microsomal incubation of KR66222 in the presence of the NADPH-generating system resulted in the formation of two metabolites, identified as S-oxidation (KR68334) and hydrolysis (KR66223) products using liquid chromatography/tandem mass spectrometry. The formation of KR66223 via an esterase and the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…Therefore, we postulate that as the concentration of peptides increased, more small peptides were released, changing the inhibition mode. Since sitagliptin is absorbed or transported intact in the intestine and in Caco-2 cells, the inhibition mode is consistent, as reported in an in vitro assay . Our results also showed that the inhibition mode of peptides could be altered by changing their physiological environment.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, we postulate that as the concentration of peptides increased, more small peptides were released, changing the inhibition mode. Since sitagliptin is absorbed or transported intact in the intestine and in Caco-2 cells, the inhibition mode is consistent, as reported in an in vitro assay . Our results also showed that the inhibition mode of peptides could be altered by changing their physiological environment.…”
Section: Discussionsupporting
confidence: 87%
“…Since sitagliptin is absorbed or transported intact in the intestine and in Caco-2 cells, the inhibition mode is consistent, as reported in an in vitro assay. 31 Our results also showed that the inhibition mode of peptides could be altered by changing their physiological environment.…”
Section: ■ Discussionsupporting
confidence: 55%
“…The cells were maintained at 37°C in a humidified atmosphere with 5% CO 2 /95% air. Cells were seeded in 12‐transwell membranes at a density of 2.5–3 × 10 5 cells and were grown for 3 weeks, replacing the culture medium every 2–3 days [16] . MDCKII‐MDR1, ‐MRP2 and –BCRP cells that overexpressed P‐gp, MRP2, and BCRP, respectively, were obtained from Dr A.H. Schinkel (Netherlands Cancer Institute, Amsterdam, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were seeded in 12-transwell membranes at a density of 2.5-3 ¥ 10 5 cells and were grown for 3 weeks, replacing the culture medium every 2-3 days. [16] MDCKII-MDR1, -MRP2 and -BCRP cells that overexpressed P-gp, MRP2, and BCRP, respectively, were obtained from Dr A.H. Schinkel (Netherlands Cancer Institute, Amsterdam, The Netherlands). The cells were grown and seeded on filter inserts at a density of 6 ¥ 10 4 cells/insert in a similar manner to that described for Caco-2 cells.…”
Section: Cell Culturementioning
confidence: 99%
“…This compound showed excellent selectivity toward DPP4 inhibition with an IC 50 value of 1 nM in vitro compared with another DDP isozyme, sitagliptin, which has an IC 50 value of 20 nM. KR-66223 is chemically and metabolically stable, and showed no CYP inhibition, hERG binding, or cytotoxicity [10,11].…”
Section: Introductionmentioning
confidence: 95%